Collisional radiative model for the evaluation of the thermal helium beam diagnostic at ASDEX upgrade. (1st April 2022) - Wendler, D; Dux, R; Fischer, R; Griener, M; Wolfrum, E; Birkenmeier, G; Stroth, U; ,
Abstract: The thermal helium beam diagnostic at ASDEX Upgrade is used to infer the electron density n e and temperature T e in the scrape-off layer and the pedestal region from the emission of visible lines of the locally injected helium. The link between n e and T e and the emission is provided by a collisional radiative model, which delivers the evolution of the populations of the relevant excited states as the He atoms travel through the plasma. A computationally efficient method with just three effective states is shown to provide a good approximation of the population dynamics. It removes an artificial rise of T e at the plasma edge when using a simple static model. Furthermore, the re-absorption of the vacuum ultra-violet resonance lines has been introduced as an additional excitation mechanism being mainly important in the region close to the injection point. This extra excitation leads to a much better fit of the measured line ratios in this region for larger puff rates.